Perilaku Shopaholic sebagai Tantangan Global dalam Perspektif Teori Difusi Inovasi - Haryani, Yunita (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon of shopaholic behavior, or compulsive buying, has emerged as a growingglobal challenge in the digital era. Advances in information technology, the convenience ofonline shopping, and constant exposure to social media have accelerated the diffusion ofconsumerist lifestyles across cultures and generations. This study aims to analyze shopaholicbehavior through the lens of Diffusion of Innovation Theory developed by Everett M. Rogers(2003). Using a qualitative approach based on literature review, the article explores howtechnological innovations are rapidly diffused within global society and contribute to thenormalization of excessive consumption behavior. The findings indicate that the innovationadoption process, through adopter categories (from innovators to laggards), strengthenscompulsive buying tendencies, especially among young users and those with low financialliteracy. Therefore, mitigation efforts must include consumer education, digital platformregulation, and the promotion of mindful consumption values through the same diffusionchannels. This study recommends cross-sector collaboration to address the negative impactsof innovation diffusion on global consumer behavior.